2014
DOI: 10.1080/00207179.2014.883464
|View full text |Cite
|
Sign up to set email alerts
|

A novel control design for delayed teleoperation based on delay-scheduled Lyapunov–Krasovskii functionals

Abstract: This paper addresses the controller design problem for bilateral teleoperation over unreliable networks. The stability and tracking performance analysis are presented for a novel force-reflecting emulator control scheme. The performance (stability, synchronization, transparency) is guaranteed by H∞ control theory and delayscheduled Lyapunov-Krasovskii functionals (LKF), which could improve the existing stability criterion. The design is achieved by using Linear Matrix Inequality (LMI) optimization. For the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…For instance, [3] focuses on time-varying control affine plants (i.e., no delay dynamics in the plant nor controller) and state feedback with a constant delay whilst neither exogenous/modeling disturbances, distorted data nor scheduling protocols are taken into account. Similar comparisons can be drawn with respect to other related works (see [1]- [6] and the references therein).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…For instance, [3] focuses on time-varying control affine plants (i.e., no delay dynamics in the plant nor controller) and state feedback with a constant delay whilst neither exogenous/modeling disturbances, distorted data nor scheduling protocols are taken into account. Similar comparisons can be drawn with respect to other related works (see [1]- [6] and the references therein).…”
Section: Introductionsupporting
confidence: 58%
“…Besides the already introduced upper bound d on d i (t)'s, we assume that d i (t)'s are differentiable with bounded |ḋ i (t)|. As orchestrated by (6), if the j th NCS link is granted access to the communication medium at some t i ∈ T , the corresponding components of (ŷ(t i ),û(t i )) jump to the received values. It is to be noted that all other components of (ŷ(t i ),û(t i )) remain unaltered.…”
Section: Problem Statementmentioning
confidence: 99%
“…Basically, we want to interconnect dynamics (8) and dynamics (10)- (11). To that end, let us expand the right side of (10):…”
Section: A Interconnecting the Nominal And Error Systemmentioning
confidence: 99%
“…Third, the obtained transmission intervals are confirmed experimentally (see Figure 1). For plant-controller settings, comprehensive theoretical and experimental studies of degraded communication environments are reported in [10] and [11]. Nevertheless, these references impose Zero-Order-Hold (ZOH) sampling and do not consider noisy data nor scheduling protocols [8], [9].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, [19] does not take into account modeling/exogenous disturbances, distorted data or scheduling protocols. The authors in [20] and [21] focus on linear control systems and Zero-Order-Hold (ZOH) sampling (rather than model-based estimation) whilst neither noisy data nor scheduling protocols are considered. It is also worth mentioning that [20] does not take into account disturbances.…”
Section: Introductionmentioning
confidence: 99%